Obstacles and Challenges of Elementary School Students in Learning Mathematics with Quizzes Media - Khanaya, Mutia Madani; Sashena, Nasya Putri; W, Wahyunengsih (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study was motivated by the difficulties experienced by elementary school stuThis research is motivated by the difficulties of elementary school students in learning mathematics in using quizzes at school. This study aims to identify and analyze the inhibiting factors that affect elementary school students in learning mathematics using quiz media. This research method combines quantitative and qualitative approaches by collecting data from questionnaires and interviews with several students. The results of the study stated that there were several students who felt obstacles and barriers to learning, such as delays in understanding basic mathematical concepts, difficulties in operating the technological devices used, time pressure that limited students to answer questions correctly and differences in abilities between students. In conclusion, the challenges and obstacles to the use of quizzes in elementary school students arise from various aspects, namely pedagogical, psychological, technical and conceptual understanding. Of the four aspects, pedagogical obstacles are the most dominant.